Importance of Free Intraperitoneal Fluid on Ultrasound in Children with Blunt Abdominal Trauma. - Nural, Mehmet Selim; Ceyhan, Meltem; Balçik, Çinar (Turkiye Klinikleri Journal of Medical Sciences, 2012)
Objective: The assessment of importance of free intraperitoneal fluid determination without solid organ injury by ultrasound (US) in children who had blunt abdominal trauma (BAT). Material and Methods: The clinical and imaging data of 230 children with BAT were reviewed retrospectively. All children underwent an abdominal US examination as the primary screening method. Patients with free intraperitoneal fluid without any solid-organ injury according to US examination were included in the study. The localization of intra-peritoneal fluid was also noted. US findings were compared with findings of computerized tomography, laparotomy and clinical course. Results: Intraperitoneal fluid was determined in 22 patients by US examination. Fluid was located in any location in the abdominal cavity with or without pelvis involvement in 11 patients, and 6 of them had intra-abdominal injury according to final diagnosis. Remaining 11 patients had only free pelvic fluid and 2 of them had pelvic wall injury. However any intra-abdominal injury was not determined in 11 patients with only free pelvic fluid (group 1), intra-abdominal injury was determined in 1 (25%) of 4 patients who had free fluid in a single intraperitoneal space except pelvis (group 2) and in 5 (71%) of 7 patients who had free fluid in any of the intra-peritoneal spaces in addition to pelvis (group 3). Intra-abdominal injury was significantly higher in group 3 when compared to group 1 (Fisher\'s exact test p=0.002). Conclusion: US is an effective screening method in hemodynamically stable patients with BAT. Clinical follow up of such patients is enough because the risk of serious intra-abdominal injury is low in patients with only free fluid in pelvis detected by US. However, the presence of free fluid in any abdominal location beyond the pelvis pelvis necessitates examination with further imaging modalities.